Facing the Frontline - An Interpretative Phenomenological Analysis of the Filipino Rural Doctors' Mental Health Amid COVID-19 - Umil, Mary Diane (Archīum Ateneo, 2023)
Global health crises impose considerable strain in health care systems worldwide that create mental health challenges among medical practitioners. Greater challenges are experienced by doctors practicing in rural areas of developing countries such as the Philippines that have weak healthcare infrastructures and meager resources for health services. Thus, this study sought to explore doctors experiences of working in rural areas during the COVID-19 pandemic and to identify contextual factors contributing to their mental health. Interpretative phenomenological analysis was used in gathering and analyzing data from semistructured interviews with 12 doctors who worked in rural areas in Eastern Visayas, a region that has very few doctors and that experienced a rise in COVID-19 cases at the time of the study. The findings revealed challenges to doctors mental health that include fear of exposure, burnout, scarcity of supplies, and patient-related challenges that reflected contextual realities in the area. The results also described coping strategies utilized by the rural doctors, e.g., communing with nature, diskarte (resourcefulness), social support from family and coworkers, and bayanihan (observed in this study as mutual support among doctors in the rural community to achieve collective goals). The findings highlight policy implications and other forms of support that will sustain rural doctors mental health amid a pandemic.